Responsiveness of clinical outcome measures in Charcot−Marie−Tooth disease. (31st July 2015) - Piscosquito, G.; Reilly, M. M.; Schenone, A.; Fabrizi, G. M.; Cavallaro, T.; Santoro, L.; Manganelli, F.; Vita, G.; Quattrone, A.; Padua, L.; Gemignani, F.; Visioli, F.; et al.
Abstract : Background and purpose: Charcot−Marie−Tooth disease (CMT) is a very slowly progressive neuropathy which makes it difficult to detect disease progression over time and to assess intervention efficacy. Experience from completed clinical trials with ascorbic acid and natural history studies confirm difficulties in detecting such changes. Consequently, sensitive‐to‐change outcome measures (OMs) are urgently needed. Methods: The relative responsiveness of clinical scales of the Italian−UK ascorbic acid trial (placebo arm) were assessed by using the standardized response mean (SRM), which is the ratio of the paired scores mean change over time to the standard deviation of the score change (0 is worst responsiveness). Results: Little worsening of OM scores was found over 2 years. In detail, the primary OM of the trial, the CMT Neuropathy Score version 1 (CMTNSv1), showed low responsiveness (SRM 0.13). Some CMTNS items showed slightly greater responsiveness (CMT Examination Score 0.17; CMTNS Signs 0.19). Myometric assessments of handgrip and foot dorsiflexion strength were the most responsive (SRM −0.31 and −0.38, respectively). Amongst the other measures, the nine‐hole peg test, which assesses upper limb functioning, showed the best sensitivity to change (SRM 0.28). Conclusions: Overall these OMs showed low or negligible responsiveness, confirming the need to improve current OMs and to develop novel ones for prognostic and interventional studies. However, handgrip and foot dorsiflexion myometry are worth retaining for future trials as they were the most responsive and are likely to be clinically relevant for patients.